Spillovers from Dollar Appreciation - Chow, Julian (Spillover Notes; Spillover Notes ;, 2016)
The recent strong, sustained appreciation of the U.S. dollar raises questions about possible financial spillover effects for emerging markets and developing countries. This report finds that, unlike past episodes, emerging markets' vulnerability has improved along a number of dimensions, though some risks persist (as identified in this report).